Decorative material
By employing a dual curing method combining ionizing radiation-cured resin and urethane-based resin, along with hydrophilic inorganic materials and silicone-based anti-sticking agents, the combination of gloss adjustment layers is optimized. This solves the design, scratch resistance, and anti-sticking issues of decorative materials when layering gloss adjustment layers, achieving excellent decorative effects.
Patent Information
- Application Number
- CN202511328227.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-07-11
- Filing Date
- 2018-07-10
- Publication Date
- 2026-01-06
AI Technical Summary
Existing decorative materials, when layered with a gloss-adjusting layer, struggle to simultaneously achieve design appeal, scratch resistance, and long-term stable non-stick properties.
A dual curing method using ionizing radiation-cured resin and urethane-based resin, combined with hydrophilic inorganic materials and silicone-based anti-sticking agents with reactive ends, optimizes the combination of gloss adjustment layers to form the first and second gloss adjustment layers.
It achieves excellent scratch resistance and long-term stable non-stick properties in decorative materials, while enhancing design, especially the texture and gloss differences, thus improving the decorative effect.
Smart Images

Figure CN121271318A_ABST
Abstract
Description
[0001] This patent application is filed in July 2018 with application number 201880044691.1.
[0002] On the 10th, a divisional application was filed for a patent application entitled "Decorative Materials". Technical Field
[0003] This invention relates to decorative materials. Background Technology
[0004] As a technology concerning decorative materials, there is, for example, the technology described in Patent Document 1.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent No. 3629964 Summary of the Invention
[0008] The problem that the invention aims to solve
[0009] Among decorative materials based on prior art, there are known materials with a layered gloss-adjusting layer, which is a synthetic coating layer that creates a textured shape by forming a beveled surface with a continuously varying depth. However, few decorative materials can layer an upper gloss-adjusting layer on a portion of the lower gloss-adjusting layer to give it a design-like appearance while also having excellent scratch resistance and long-term stable non-stick properties.
[0010] To address the aforementioned issues, the present invention aims to provide a decorative material in which an upper gloss adjustment layer is layered on a portion of a lower gloss adjustment layer to provide design flexibility, while also exhibiting excellent scratch resistance and long-term stable non-stick properties.
[0011] Methods for solving problems
[0012] The inventors designed the resin composition of the gloss adjustment layer to be a dual-curing method combining ionizing radiation-cured resin and urethane resin, and optimized the reactive ends of the gloss modifier and silicone anti-stick agent added to each gloss adjustment layer. In other words, various studies and experiments were conducted on the preferred combination, and it was found that a decorative material with excellent scratch resistance and long-term stable anti-stick properties can be provided.
[0013] To achieve the objective, a decorative material according to one aspect of the present invention comprises a first gloss adjusting layer disposed on the surface side and a second gloss adjusting layer disposed on a portion of the first gloss adjusting layer, wherein the first gloss adjusting layer comprises a gloss adjusting agent composed of a hydrophilic inorganic material and an organosilicon-based anti-sticking agent having reactive ends.
[0014] Here, hydrophilic inorganic materials refer to inorganic materials with hydrophilic surfaces. A representative example of a hydrophilic inorganic material is silica that has not undergone surface treatment or modification, i.e., silica without hydrophobic treatment of its surface.
[0015] The effects of the invention
[0016] According to one aspect of the invention, by selecting the type of gloss modifier added to the underlying gloss modifier layer (i.e., the first gloss modifier layer) and by giving the silicone-based anti-stick agent a reactive end, a decorative material with long-term stable anti-stick properties can be provided. In other words, according to one aspect of the invention, a decorative material can be provided in which an upper gloss modifier layer is laminated on a portion of the lower gloss modifier layer to provide design flexibility, while also exhibiting excellent scratch resistance and achieving long-term stable anti-stick properties. Brief description of the attached figures
[0017] [ Figure 1 [This is a cross-sectional view showing the composition of the decorative material according to an embodiment of the present invention.]
[0018] [ Figure 2 [This is a cross-sectional view showing the composition of a decorative material according to a modified example of an embodiment of the present invention.] Detailed Implementation
[0019] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings.
[0020] The accompanying drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each layer, etc., differ from actual conditions. Furthermore, the embodiments shown below illustrate configurations for embodying the technical concept of the present invention; however, the materials, shapes, and structures of the constituent parts are not limited to those described below. The technical concept of the present invention can be modified in various ways within the scope of the claims as defined in the claims.
[0021] (constitute)
[0022] The decorative material 1 in this embodiment has a gloss-adjusting layer on the surface side, such as... Figure 1As shown, the gloss adjustment layer includes a first gloss adjustment layer 5 located below as the bottom layer, and a second gloss adjustment layer 6 disposed on a portion of the first gloss adjustment layer 5 to improve design.
[0023] Between the substrate 2 and the first gloss adjustment layer 5, it may also be configured with other known layers such as a bottom solid ink layer 3, a patterned ink layer 4, and a transparent resin layer (not shown).
[0024] <Gloss Adjustment Layer>
[0025] The first gloss adjustment layer 5 is disposed above the underlying solid ink layer 3 and the patterned ink layer 4, and is used to adjust the gloss state of the surface of the decorative material 1. The first gloss adjustment layer 5 is formed on the entire surface side of the underlying solid ink layer 3 and the patterned ink layer 4. Figure 1 The first gloss adjustment layer 5 is placed on the upper surface of the first gloss adjustment layer 5 and covers the entire surface of the substrate 2. A second gloss adjustment layer 6 is disposed above the first gloss adjustment layer 5 and has a different gloss level than the first gloss adjustment layer 5; it is used to adjust the gloss state of the surface of the decorative material 1. The second gloss adjustment layer 6 is formed on a portion of the surface of the first gloss adjustment layer 5. Furthermore, the gloss difference between these first and second gloss adjustment layers 5 and 6 allows for the creation of textured surfaces and enhances design flexibility.
[0026] The thickness of the first and second gloss adjustment layers 5 and 6 is preferably 1 μm to 15 μm. Furthermore, since the first and second gloss adjustment layers 5 and 6 form the outermost surface of the decorative material 1, they need to possess surface properties such as abrasion resistance, scratch resistance, and solvent resistance required for the decorative material 1. Abrasion resistance and scratch resistance are influenced by thickness, with greater thickness being more advantageous. Therefore, a more preferred thickness for the first and second gloss adjustment layers 5 and 6 is 2 μm to 12 μm. When the thickness is less than 1 μm, the abrasion resistance and scratch resistance significantly deteriorate, thus limiting their use as decorative material 1. Additionally, when the thickness is greater than 15 μm, the flexibility of the first and second gloss adjustment layers 5 and 6 decreases, thus reducing their processability as decorative material 1.
[0027] The first and second gloss adjustment layers 5 and 6 each contain at least a resin material and a gloss modifier and an anti-sticking agent added to the resin material. It should be noted that the gloss modifier may be added only to the first gloss adjustment layer 5, which has a relatively low gloss level.
[0028] [Resin Composition]
[0029] The resin materials constituting the first and second gloss adjustment layers 5 and 6 preferably have sufficient transparency to allow visual identification of the underlying layer.
[0030] The main material of the transparent resin used in the first gloss adjustment layer 5 is preferably a mixture of a 2-component urethane thermosetting resin having various polyols and isocyanates, and an ionizing radiation-curing resin having acryloyl or methacryloyl groups. In this case, it is preferable to include 3 to 100 parts by mass of urethane thermosetting resin relative to 100 parts by mass of ionizing radiation-curing resin, more preferably 10 to 50 parts by mass. With this configuration, by irradiating the decorative material 1 with ionizing radiation after preparation, the ionizing radiation-curing resin constituting the resin component can be cured, thereby improving the scratch resistance of the first gloss adjustment layer 5. Furthermore, by setting the urethane thermosetting resin to 10 to 50 parts by mass relative to 100 parts by mass of ionizing radiation-curing resin, it is possible to significantly eliminate both the defects encountered when the second gloss adjustment layer 6 is laminated and the scratch resistance of the first gloss adjustment layer 5.
[0031] Here, when the proportion of urethane-based thermosetting resin is less than 3 parts by mass, the first gloss adjusting layer 5 is prone to dissolution or scratching when the second gloss adjusting layer 6 is laminated. On the other hand, when the proportion of urethane-based thermosetting resin exceeds 100 parts by mass, the scratch resistance of the first gloss adjusting layer 5 is significantly reduced due to the decreased crosslinking degree of the resin composition.
[0032] Thus, the decorative material 1 according to this embodiment can exhibit high scratch resistance while suppressing adverse conditions during lamination.
[0033] In this specification, the main material refers to a resin material with a content of 90 parts by mass or more, preferably 97 parts by mass or more, relative to 100 parts by mass of all resin components constituting the target layer.
[0034] Furthermore, the main material constituting the resin component of the second gloss adjustment layer 6 is preferably a mixture of a urethane-based thermosetting resin having polyols and isocyanates, and an ionizing radiation-curing resin having acryloyl or methacryloyl groups. In this case, it is preferable to include 25 parts by weight or less of a urethane-based thermosetting resin relative to 100 parts by weight of the ionizing radiation-curing resin.
[0035] When the proportion of urethane-based thermosetting resin exceeds 25 parts by mass, the excessive proportion of urethane-based thermosetting resin reduces the degree of crosslinking of the resin composition, significantly decreasing the scratch resistance of the second gloss adjustment layer 6. When the proportion of urethane-based thermosetting resin is less than 3 parts by mass, the required properties (prevention of cracking) for decorative materials 1 are sometimes not met. Furthermore, by setting the urethane-based thermosetting resin in the second gloss adjustment layer 6 to 25 parts by mass or less, irradiation with ionizing radiation after the preparation of the decorative material 1 allows the ionizing radiation-curing resin constituting the resin component to be fully cured, thereby improving the scratch resistance of the second gloss adjustment layer 6.
[0036] Alternatively, the main material constituting the resin component of the second gloss adjustment layer 6 may also be an ionizing radiation-cured resin having acryloyl or methacryloyl groups. In this case, the resin component constituting the second gloss adjustment layer 6 is preferably only an ionizing radiation-cured resin having acryloyl or methacryloyl groups.
[0037] Here, as the aforementioned ionizing radiation-curing resin having acryloyl or methacryloyl groups, various known materials such as monomers or commercially available oligomers can be used. For the ionizing radiation-curing resin having acryloyl or methacryloyl groups according to embodiments of the present invention, it is preferable to use, for example, multifunctional monomers such as pentaerythritol triacrylate (PET3A), pentaerythritol tetraacrylate (PET4A), trimethylolpropane triacrylate (TMPTA), dipentaerythritol hexaacrylate (DPHA), multifunctional oligomers such as "UV-1700B" manufactured by Nippon Synthetic Chemicals, or mixtures thereof.
[0038] Furthermore, as the isocyanate in the aforementioned urethane-based thermosetting resins containing polyols and isocyanates, curing agents such as derivatives of toluene diisocyanate (TDI), xylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), diphenylmethane diisocyanate (MDI), lysine diisocyanate (LDI), isophorone diisocyanate (IPDI), methyl hexane diisocyanate (HTDI), bis(methyl isocyanate)cyclohexane (HXDI), and trimethyl hexamethylene diisocyanate (TMDI), such as adducts, biuret forms, and isocyanurate forms, can be used. Additionally, as the polyol, examples include acrylic polyols, polycarbonate polyols, and polyester polyols.
[0039] Furthermore, as the ionizing radiation-curable resin constituting the first and second gloss adjustment layers 5 and 6, and having acryloyl or methacryloyl groups, it is preferable to use a polyfunctional (meth)acrylate monomer or oligomer with a number average molecular weight of 300 to 5000 and a functional group number or average functional group number of 4 to 15. By setting it to this range, the crosslinking degree of the resin component in the gloss adjustment layer can be sufficiently increased, thereby achieving high scratch resistance. Furthermore, it is more preferable to use a polyfunctional (meth)acrylate monomer with a number average molecular weight of 300 to 1500 and a functional group number or average functional group number of 4 to 8. By setting it to this range, the viscosity of the ionizing radiation-curable resin itself can be reduced, thus increasing the solid component concentration at this viscosity when preparing the ink for forming the gloss adjustment layer, improving the stability of the ink itself, and improving the coating condition. In addition, examples of polyfunctional (meth)acrylate monomers include: pentaerythritol tetra(meth)acrylate (PET4A) and its modified forms, di(trimethylolpropane)tetra(meth)acrylate and its modified forms, dipentaerythritol penta(meth)acrylate (DPPA) and its modified forms, and dipentaerythritol hexa(meth)acrylate (DPHA) and its modified forms.
[0040] There are no particular limitations on the method for determining the number-average molecular weight of the above-mentioned ionizing radiation-cured resin, but gel permeation chromatography (GPC) is preferred. While there are no particular limitations on the GPC apparatus, the packing material for the GPC column is preferably polystyrene gel, and tetrahydrofuran (THF) is preferably used as the eluent. Furthermore, the GPC standard can be, for example, a polystyrene polymer. It should be noted that for the above-mentioned polyfunctional (meth)acrylate monomers, since they are composed of monomers, if their structure is known, the number-average molecular weight can be the value calculated from the structural formula.
[0041] [Gloss Modifier]
[0042] In this embodiment, as a gloss modifier added at least to the first gloss modifying layer 5, microparticles of an inorganic material having a hydrophilic surface (hydrophilic inorganic material) are used.
[0043] As a hydrophilic inorganic material, known inorganic materials that have not undergone surface treatment or modification (i.e., have not been hydrophobically treated) can be used. Examples of gloss modifiers that can constitute such hydrophilic inorganic materials include microparticles composed of inorganic materials such as silica, glass, alumina, calcium carbonate, and barium sulfate. The surface of inorganic materials that have not undergone surface treatment or modification retains many hydroxyl groups, thus exhibiting hydrophilicity. On the other hand, the added silicone-based anti-stick agent is hydrophobic. Therefore, the silicone-based anti-stick agent will not adsorb onto the surface of the inorganic material but will instead be repelled, thus increasing the tendency for the silicone-based anti-stick agent to be unevenly distributed on the surface of the gloss-modifying layer. As a result, sufficient anti-stick properties can be achieved with a small amount of silicone-based anti-stick agent.
[0044] Even if a hydrophilic inorganic material has undergone some surface treatment or surface modification, it can be any silica with a hydrophilic surface. For example, as the hydrophilic inorganic material of this embodiment, it is preferred to be an inorganic material that satisfies [(value of evaluation method B / value of evaluation method A) < 1.2] in the following two evaluation methods A and B.
[0045] • Evaluation Method A (Heat Loss Evaluation)
[0046] The gloss modifier was heated to 110°C, and the mass loss was measured. First, a mass loss occurred due to the desorption of moisture adsorbed on the surface of the gloss modifier. On the other hand, even with surface treatment, since the component does not desorb and volatilize at 110°C, the numerical difference caused by surface treatment is the same if the raw material of the gloss modifier is the same. However, since the amount of moisture adsorbed depends on the manufacturing method of the gloss modifier, this value varies depending on the gloss modifier.
[0047] In the specific measurement method, according to JIS K5101,23, the sample is placed at 110°C for a sufficient time (e.g., 2 hours) and then the mass loss is measured.
[0048] • Evaluation Method B (Loss on Ignition Evaluation)
[0049] The material was heated to 950°C, and the mass loss was measured. By heating to 950°C, organic matter treated (adhered) to the surface of the gloss modifier detached from it. Therefore, if the temperature was maintained at 950°C, the mass loss of the surface-treated gloss modifier was greater than that of the untreated gloss modifier. This difference represents the amount of surface treatment.
[0050] In the specific measurement method, as described above, the sample is placed in an environment of 950°C for a sufficient time (e.g., 2 hours), and then the mass loss is measured.
[0051] Furthermore, if an inorganic material satisfies the condition [(value of evaluation method B / value of evaluation method A) < 1.2], then even if some surface treatment or surface modification is performed, it can be presumed to have the same hydrophilicity as inorganic materials that have not undergone surface treatment or surface modification, and such inorganic materials have many residual hydroxyl groups on their surface, thus exhibiting hydrophilicity.
[0052] Here, when a gloss modifier is also added to the second gloss adjustment layer 6, the gloss modifier is preferably a hydrophilic inorganic material, but commercially available and known gloss modifiers can also be used. For example, microparticles composed of inorganic materials such as silica, glass, alumina, calcium carbonate, and barium sulfate, the same as those added to the first gloss adjustment layer 5, can also be used. Alternatively, microparticles composed of organic materials such as acrylics can also be used. However, when high transparency is required, it is desirable to use microparticles such as silica, glass, and acrylics with high transparency. In particular, gloss modifiers with low bulk density, formed by the secondary aggregation of fine primary particles rather than solid spherical particles, have a high matting effect relative to the amount added. Therefore, by using such a gloss modifier, a gloss adjustment layer with lower gloss can be formed. As a result, the gloss difference between the first gloss adjustment layer 5 and the second gloss adjustment layer 6 can be increased, and the resulting texture can be enhanced. As a result, superior design expression with greater depth can be achieved.
[0053] The particle size of the gloss modifier can be selected from any value, but is preferably set to 2μm or more and 15μm or less. More preferably, it is 4μm or more and 12μm or less. Gloss modifiers with a particle size of less than 2μm have a low matting effect, and therefore sometimes cannot fully achieve the unevenness caused by the gloss difference. On the other hand, gloss modifiers with a particle size of more than 15μm cause greater light scattering, which can cause the layers containing the gloss modifier in the first and second gloss modifier layers 5 and 6 to become cloudy or have a larger visual graininess, and thus sometimes, in turn, impair the unevenness caused by the gloss difference.
[0054] [Anti-sticking agent]
[0055] Since the decorative material 1 of this embodiment needs to have long-term stable non-stick properties, it is important to add a silicone-based anti-stick agent with reactive ends to the first gloss adjustment layer 5. It should be noted that the silicone-based anti-stick agent also functions as a slip agent.
[0056] In particular, silicone-based anti-sticking agents having hydroxyl or amino groups, or both, as reactive terminals are preferred. In this case, regarding the structure of the silicone framework, the reactive terminals can be appropriately selected considering compatibility with resins and solvents when mixed to form a coating agent, and there is no particular limitation on the type. Since a urethane-based thermosetting resin is used as the resin constituting the first gloss adjustment layer 5, long-term stable anti-sticking properties can be exhibited by introducing hydroxyl or amino groups into the resin framework during the urethane curing reaction.
[0057] Relative to 100 parts by weight of the total solids composition of the first gloss adjustment layer 5, the amount of the aforementioned silicone-based anti-stick agent containing hydroxyl or amino groups is preferably 1 to 6 parts by weight as an effective component of the silicone-based anti-stick agent. If it is less than 1 part by weight, it is difficult to exhibit the desired anti-stick properties; if it is more than 6 parts by weight, a portion of the silicone-based anti-stick agent will not be introduced into the resin matrix, and it may not be able to stably exhibit anti-stick properties over a long period of time.
[0058] The anti-sticking agent added to the second gloss adjustment layer 6 is preferably a silicone-based anti-sticking agent with reactive terminals. Importantly, this silicone-based anti-sticking agent has acryloyl or methacryloyl groups, or both, as reactive terminals. Similar to the first gloss adjustment layer 5 described above, the type of silicone backbone is not particularly limited. Furthermore, relative to 100 parts by weight of the total solids constituting the second gloss adjustment layer 6, the amount of silicone-based anti-sticking agent having acryloyl or methacryloyl groups, or both, added is preferably between 0.5 and 5 parts by weight as an effective component of the silicone-based anti-sticking agent. If it is less than 0.5 parts by weight, it is difficult to exhibit the desired anti-sticking properties; if it exceeds 5 parts by weight, a portion of the silicone-based anti-sticking agent will not be introduced into the resin backbone, and it may not be able to stably exhibit anti-sticking properties over a long period.
[0059] The amount of gloss modifier added relative to 100 parts by weight is preferably 5 parts by weight or more and 40 parts by weight or less. More preferably, it is set to 10 parts by weight or more and 30 parts by weight or less. If it is less than 5 parts by weight, the gloss difference between the gloss modifier and the relatively high gloss layer will be small due to insufficient matting effect, and the texture may sometimes be insufficient. In addition, if it is more than 40 parts by weight, the resin composition becomes relatively insufficient relative to the gloss modifier, which will lead to the gloss modifier peeling off and the scratch resistance caused by peeling off, which will greatly impair the durability required by the decorative material 1.
[0060] It should be noted that any gloss modifier can be added to the gloss adjustment layer with a relatively high gloss. These need to be adjusted appropriately according to the final texture or design. In addition, the gloss modifier and resin composition used for the first and second gloss adjustment layers 5 and 6 can be the same or different. These can be freely selected according to the texture and various desired properties.
[0061] [Other Additives]
[0062] In addition, to impart various functions to the first and second gloss adjustment layers 5 and 6, functional additives such as antibacterial agents and antifungal agents can be added. Furthermore, ultraviolet absorbers and light stabilizers can be added as needed. Examples of ultraviolet absorbers include benzotriazole, benzoate, benzophenone, triazine, and cyanoacrylate series. Examples of light stabilizers include hindered amine series.
[0063] <Substrate>
[0064] The substrate 2 is not particularly limited as long as it is the base paper used for decorative material 1. For example, it can be any type of paper such as tissue paper, resin-blended paper, titanium paper, resin-impregnated paper, flame-retardant paper, or inorganic paper; woven or nonwoven fabrics made of natural or synthetic fibers; polyolefin resins such as homopolymer or atactic polypropylene resin and polyethylene resin; synthetic resin-based substrates such as copolymer polyester resin, amorphous crystalline polyester resin, polyethylene naphthalate resin, polybutene resin, acrylic resin, polyamide resin, polycarbonate resin, polyvinylidene chloride resin, and fluoropolymer resin; wood-based substrates such as veneer, plywood, laminate, particleboard, and medium-density fiberboard; inorganic substrates such as gypsum board, cement board, calcium silicate board, and ceramic board; metal-based substrates such as iron, copper, aluminum, and stainless steel; or composite materials and laminates thereof, as well as other conventionally known materials. Furthermore, the shape of the substrate 2 can be, for example, film, sheet, plate, or irregularly shaped form.
[0065] <Patterned Ink Layer>
[0066] It should be noted that a patterned ink layer 4 for applying patterns to the decorative material 1 can be provided between the substrate 2 and the first gloss adjustment layer 5. Examples of patterns that can be used include wood grain, stone grain, sand grain, tile, brickwork, fabric, leather, and geometric shapes. Figure 1In the example, the patterned ink layer 4 is formed directly below the second gloss adjustment layer 6. In other words, the second gloss adjustment layer 6 is formed only in the portion overlapping with the patterned ink layer 4. Furthermore, the pattern of the patterned ink layer 4 is synchronized with the gloss of the second gloss adjustment layer 6. Therefore, the design elements provided by the second gloss adjustment layer 6 can be added to the design elements provided by the patterned ink layer 4. Thus, a decorative material 1 with a design expression approaching the high-end feel of natural wood or natural stone can be formed. Here, "synchronization" refers to at least a portion of the second gloss adjustment layer 6 overlapping the patterned ink layer 4 in a plan view. It should be noted that a high degree of synchronization can be visually recognized as long as more than 50% of the area of the area where the second gloss adjustment layer 6 is formed overlaps with the patterned ink layer 4 in a plan view.
[0067] It should be noted that although this embodiment shows an example where the second gloss adjustment layer 6 is formed only in the portion overlapping with the pattern ink layer 4 (i.e., only in the portion directly above the pattern ink layer 4), other structures may also be used. For example, in a plan view (viewed from the surface side), the second gloss adjustment layer 6 can be formed only in the portion overlapping with the pattern ink layer 4; in addition to the portion directly above the pattern ink layer 4, the second gloss adjustment layer 6 may also be formed in a portion other than directly above it.
[0068] <Underlying solid ink layer>
[0069] Furthermore, depending on the desired design level, a solid ink layer 3 can be provided between the substrate 2 and the patterned ink layer 4. The solid ink layer 3 is configured to cover the entire surface of the side of the substrate 2 facing the first gloss adjustment layer 5. Additionally, depending on requirements such as concealment, the solid ink layer 3 can be multiple layers, either two or more. Furthermore, to achieve the desired design, the patterned ink layer 4 can also be formed by stacking a necessary number of individual sheets. Thus, the patterned ink layer 4 and the solid ink layer 3 can be combined in various ways depending on the desired design (i.e., the design to be represented), but there are no particular limitations.
[0070] The constituent materials of the underlying solid ink layer 3 and the patterned ink layer 4 are not particularly limited. For example, printing inks or coating agents obtained by dissolving and dispersing the matrix and colorants such as dyes and pigments in a solvent can be used. As the matrix, various synthetic resins, or mixtures or copolymers thereof, can be used, such as oil-based nitrocellulose resin, urethane resin, acrylic resin, styrene resin, polyester resin, urethane resin, polyvinyl resin, alkyd resin, epoxy resin, melamine resin, fluorinated resin, silicone resin, and rubber resin. In addition, as the colorant, inorganic pigments such as carbon black, titanium dioxide, zinc dioxide, iron oxide red, chrome yellow, Prussian blue, and cadmium red, or organic pigments such as azo pigments, lake pigments, anthraquinone pigments, phthalocyanine pigments, isoindolinone pigments, and dioxazine pigments, or mixtures thereof, can be used. Alternatively, as solvents, toluene, xylene, ethyl acetate, butyl acetate, methanol, ethanol, isopropanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, water, or mixtures thereof can be used.
[0071] In addition, in order to impart various functions to the underlying solid ink layer 3 and the patterned ink layer 4, functional additives such as extender pigments, plasticizers, dispersants, surfactants, adhesives, adhesive aids, drying agents, curing agents, curing accelerators and curing delays can also be added.
[0072] Here, the underlying solid ink layer 3, the patterned ink layer 4, and the first and second gloss adjustment layers 5 and 6 can all be formed using various printing methods, such as gravure printing, offset printing, screen printing, electrostatic printing, and inkjet printing. Furthermore, to cover the entire surface of the side surface of the substrate 2, the underlying solid ink layer 3 and the first gloss adjustment layer 5 can also be formed using various coating methods, such as roller coating, knife coating, microgravure coating, and die coating. These printing and coating methods can be selected individually depending on the layers being formed, or the same method can be used together for processing.
[0073] When adjusting the thickness of the first and second gloss adjustment layers 5 and 6, the coating amount can be adjusted simply by using the printing and coating methods described above. Samples with gloss adjustment layers formed on the substrate 2 and samples without gloss adjustment layers formed on the substrate 2 were produced using various printing and coating methods, and the coating amount can be calculated from their mass difference.
[0074] <Transparent resin layer>
[0075] In cases where particular abrasion resistance is required, a transparent resin layer (not shown) can be provided between the patterned ink layer 4 and the first gloss adjustment layer 5. As the transparent resin layer, a resin composition with an olefin-based resin as the main material is preferably used, for example. As the olefin-based resin, in addition to, for example, polypropylene, polyethylene, polybutene, etc., α-olefins (e.g., propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, trideene, 1-tetradecene, 1-pentadene, 1-hexadecene, 1-heptadecene, 1-octadecaene, 1-nonadecaene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1- Substances obtained by homopolymerization or copolymerization of two or more monomers, such as pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene; or substances obtained by copolymerizing ethylene or α-olefins with monomers other than those found in ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ethylene-methyl methacrylate copolymers, ethylene-ethyl methacrylate copolymers, ethylene-butyl methacrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-butyl acrylate copolymers. In particular, when further improvement in surface strength is desired, highly crystalline polypropylene is preferred (for example).
[0076] Additionally, additives such as heat stabilizers, UV absorbers, light stabilizers, anti-blocking agents, catalyst traps, and colorants can be added to the transparent resin layer. These additives can be appropriately selected from known additives. The transparent resin layer can be formed by various lamination methods, such as hot pressing, extrusion lamination, and dry lamination.
[0077] (Functions and others)
[0078] (1) The decorative material 1 of this embodiment includes a first gloss adjustment layer 5 and a second gloss adjustment layer 6 disposed on a portion of the first gloss adjustment layer 5. As a result, it has excellent design flexibility.
[0079] Furthermore, in the decorative material 1 of this embodiment, since the pattern of the patterned ink layer 4 is synchronized with the gloss of the second gloss adjustment layer 6, the design brought by the second gloss adjustment layer 6 can be added to the design brought by the patterned ink layer 4, and a decorative material 1 with a design expression that is close to that of natural wood or natural stone can be formed.
[0080] (2) In the decorative material 1 of this embodiment, the first gloss adjustment layer 5 on the bottom side includes a gloss adjuster made of hydrophilic inorganic material and an organosilicon anti-sticking agent with reactive ends.
[0081] At this point, the reactive terminal of the organosilicon-based anti-adhesive preferably has at least one of hydroxyl and amino groups.
[0082] Based on this composition, by employing a hydrophilic gloss modifier and a hydrophobic silicone-based anti-stick agent, the tendency of the silicone-based anti-stick agent to be unevenly distributed on the surface of the gloss modifier layer is increased. As a result, sufficient anti-stick properties can be achieved with a small amount of silicone-based anti-stick agent. In addition, by using inorganic materials such as silica as gloss modifiers, excellent transparency can be exhibited, thereby improving the visual recognition of the underlying layer.
[0083] Therefore, a decorative material 1 can be provided that has excellent visual recognition of the underlying layer and long-term stable non-stick properties.
[0084] (3) Furthermore, in the decorative material 1 of this embodiment, a gloss modifier composed of an inorganic material with a high matting effect is used. Therefore, the gloss of the added gloss modifier layer can be significantly reduced. Therefore, the difference between the gloss of the first gloss modifier layer 5 and the gloss of the second gloss modifier layer 6 can be increased, and the resulting texture can be enhanced. As a result, a superior design expression with greater depth can be achieved.
[0085] (4) In the decorative material 1 of this embodiment, the resin component constituting the first gloss adjustment layer 5 is a mixture of a 2-liquid urethane thermosetting resin having various polyols and isocyanates, and an ionizing radiation curing resin having acryloyl or methacryloyl groups. The mixing ratio of the above thermosetting resin is set to 3 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of ionizing radiation curing resin.
[0086] Based on this configuration, the first gloss adjustment layer 5 achieves a dual curing method of thermosetting and ionizing radiation curing, thereby providing a decorative material 1 that does not produce adverse effects when the second gloss adjustment layer 6 is laminated, but has excellent scratch resistance.
[0087] (Modified Example)
[0088] (1) As Figure 1 As shown in this embodiment, an example is shown where the second gloss adjustment layer 6 is formed at the portion overlapping with the pattern ink layer 4, and the pattern of the pattern ink layer 4 is synchronized with the gloss of the second gloss adjustment layer 6. However, other configurations may also be used.
[0089] For example, such as Figure 2As shown, the second gloss adjustment layer 6 can be formed on the portion other than directly above the patterned ink layer 4, and the pattern of the patterned ink layer 4 is synchronized with the gloss of the first gloss adjustment layer 5. Therefore, the gloss of the exposed first gloss adjustment layer 5 can be imparted to the pattern of the patterned ink layer 4, and the design aspect brought by the first gloss adjustment layer 5 can be added to the design aspect brought by the patterned ink layer 4. Thus, a decorative material 1 with a design expression approaching the high-end feel of natural wood or natural stone can be formed. Here, "synchronization" in this variation means that at least a portion of the first gloss adjustment layer 5 overlaps with the patterned ink layer 4 in a plan view. It should be noted that in a plan view, a high degree of synchronization can be visually recognized as long as more than 50% of the area of the first gloss adjustment layer 5 overlaps with the patterned ink layer 4.
[0090] (2) Although the example shows a mixture of a urethane thermosetting resin having polyol and isocyanate and an ionizing radiation curing resin having acryloyl or methacryloyl groups, other compositions may also be used.
[0091] For example, the resin component constituting the second gloss adjustment layer 6 can be set to an ionizing radiation-cured resin having acryloyl or methacryloyl groups. This improves the scratch resistance of the second gloss adjustment layer 6.
[0092] [Example]
[0093] Hereinafter, a specific embodiment of the decorative material 1 of this embodiment will be described.
[0094] (Example 1)
[0095] In Example 1, a weight per unit area of 50 g / m² was used. 2 Impregnated paper (GFR-506, manufactured by "Kojin Co., Ltd.") was used as substrate 2. Furthermore, an underlayer solid ink layer 3 and a patterned ink layer 4 were sequentially formed on one surface of substrate 2 using oil-based nitrocellulose resin-based gravure printing ink (PCNT (PCRNT) colors, manufactured by "Toyo Inki Co., Ltd."). The pattern of the patterned ink layer 4 was set as a wood grain pattern.
[0096] Next, on the substrate 2 where the patterned ink layer 4 is formed, ink for the first gloss adjustment layer 5 is applied (coated) to cover the entire surface of one side of the substrate 2, thereby forming the first gloss adjustment layer 5. The ink consists of 100 parts by weight (100 parts by weight of solids) of ionizing radiation-curable resin (dipentaerythritol hexaacrylate) (100% solids), 25 parts by weight of a total solids content, 54.8 parts by weight (20 parts by weight of solids) of acrylic polyol (6KW-700 (36.5% solids): manufactured by Taisei Finkemica Co., Ltd.), and 6.9 parts by weight (5 parts by weight of solids) of polyisocyanate (UR190B curing agent (72.5% solids)). The ink consists of two parts by weight of a urethane thermosetting resin (manufactured by Toyo Inki Co., Ltd.), 10 parts by weight of an untreated silica-based matting agent (Mizusawa Chemical Co., Ltd.) (total solids content: 135 parts), 5 parts by weight of an ultraviolet radical initiator (IRGACURE184, manufactured by BASF), and 4.3 parts by weight (0.8 parts by weight of active ingredient relative to total solids content) of a hydroxyl-containing silicone-based anti-sticking agent (BYK-SILCLEAN 3700 (25% active ingredient): manufactured by BYK). The ink coating weight is set to 5 g / m². 2 .
[0097] Next, without irradiating the resin component (ionizing radiation-cured resin) constituting the first gloss adjustment layer 5 with ionizing radiation, the ink for the second gloss adjustment layer 6 is applied (coated) to the portion of the first gloss adjustment layer 5 located directly above the patterned ink layer 4, thereby forming the second gloss adjustment layer 6. The ink is composed of 100 parts by weight (100 parts by weight of solids) of ionizing radiation-curing resin (dipentaerythritol hexaacrylate (100% solids)), 5 parts by weight of untreated silica-based matting agent (Mizusawa Chemical Co., Ltd.) (total solids are 105 parts), 5 parts by weight of ultraviolet radical initiator (IRGACURE184: BASF), and 0.8 parts by weight (0.3 parts by weight of active ingredient relative to total solids) of acryloyl-based silicone anti-sticking agent (BYK-UV3505 (40% active ingredient): BYK).
[0098] Then, the decorative material 1 obtained by this method is irradiated with ionizing radiation to crosslink and cure the ionizing radiation-cured resin of the first and second gloss adjustment layers 5 and 6, and further subjected to heat aging to produce the decorative material of Example 1.
[0099] (Example 2)
[0100] In Example 2, for the ink used in the first gloss adjustment layer 5, a hydroxyl-containing silicone-based anti-stick agent (BYK-SILCLEAN 3700 (25% active ingredient): manufactured by BYK) was set at 5.4 parts by weight (1.0 part of active ingredient relative to the total solids content), and for the ink used in the second gloss adjustment layer 6, an acryloyl-containing silicone-based anti-stick agent (BYK-UV3505 (40% active ingredient): manufactured by BYK) was set at 1.3 parts by weight (0.5 part of active ingredient relative to the total solids content). Apart from the above, the other components were the same as in Example 1, and the decorative material of Example 2 was produced.
[0101] (Example 3)
[0102] In Example 3, for the ink used in the first gloss adjustment layer 5, 10.8 parts by weight of a hydroxyl-containing silicone-based anti-stick agent (BYK-SILCLEAN 3700 (25% active ingredient): manufactured by BYK) was used (2.0 parts by weight relative to the total solids content). For the ink used in the second gloss adjustment layer 6, 5.3 parts by weight of an acryloyl-containing silicone-based anti-stick agent (BYK-UV3505 (40% active ingredient): manufactured by BYK) was used (2.0 parts by weight relative to the total solids content). Apart from the above, the other components were the same as in Example 1, and the decorative material of Example 3 was produced.
[0103] (Example 4)
[0104] In Example 4, the ink used for the second gloss adjustment layer 6 comprises 25 parts by weight of an ionizing radiation-curing resin (dipentaerythritol hexaacrylate (100% solid content)) with a total solid content of 54.8 parts by weight of acrylic polyol (6KW-700 (36.5% solid content): manufactured by Taisei Finkemica Co., Ltd.) and 6.9 parts by weight of polyisocyanate (UR190B curing agent (72.5% solid content): manufactured by Toyo Inki Co., Ltd.) with a total solid content of 100 parts by weight (100 parts by weight of solid content). The decorative material of Example 4 was prepared by comprising 2 parts by weight of a urethane thermosetting resin, 5 parts by weight of an untreated silica-based matting agent (Mizusawa Chemical Co., Ltd.) (total solids content: 130 parts), 5 parts by weight of an ultraviolet radical initiator (IRGACURE184: BASF), and 6.5 parts by weight (2.0 parts by weight of active ingredient relative to total solids content) of an acryloyl-based silicone anti-sticking agent (BYK-UV3505 (40% active ingredient): BYK). Except for the above, the other components were the same as in Example 3, and the decorative material of Example 4 was prepared.
[0105] (Example 5)
[0106] In Example 5, for the ink used in the first gloss adjustment layer 5, 27.0 parts by weight of a hydroxyl-containing silicone-based anti-stick agent (BYK-SILCLEAN 3700 (25% active ingredient): manufactured by BYK) was used (5.0 parts of active ingredient relative to the total solids content), and for the ink used in the second gloss adjustment layer 6, 11.8 parts by weight of an acryloyl-containing silicone-based anti-stick agent (BYK-UV3505 (40% active ingredient): manufactured by BYK) was used (4.5 parts of active ingredient relative to the total solids content). Apart from the above, the other components were the same as in Example 1, and the decorative material of Example 5 was produced.
[0107] (Example 6)
[0108] In Example 6, for the ink used in the first gloss adjustment layer 5, a hydroxyl-containing silicone-based anti-stick agent (BYK-SILCLEAN 3700 (25% active ingredient): manufactured by BYK) was set at 35.1 parts by weight (6.5 parts of active ingredient relative to the total solids content), and for the ink used in the second gloss adjustment layer 6, an acryloyl-containing silicone-based anti-stick agent (BYK-UV3505 (40% active ingredient): manufactured by BYK) was set at 14.5 parts by weight (5.5 parts of active ingredient relative to the total solids content). Apart from the above, the other components were the same as in Example 1, and the decorative material of Example 6 was produced.
[0109] (Comparative Example 1)
[0110] In Comparative Example 1, for the ink used in the first gloss adjustment layer 5, 2.6 parts by weight of a non-reactive silicone-based anti-stick agent (BYK-330 (51% active ingredient): manufactured by BYK) was used (1.0 part of active ingredient relative to the total solids content), and for the ink used in the second gloss adjustment layer 6, 1.0 part by weight of a non-reactive silicone-based anti-stick agent (BYK-330 (51% active ingredient): manufactured by BYK) was used (0.5 part of active ingredient relative to the total solids content). Apart from the above, the other components were the same as in Example 1, and the decorative material of Comparative Example 1 was produced.
[0111] (Comparative Example 2)
[0112] In Comparative Example 2, the ink used for the first gloss adjustment layer 5 contained 5.3 parts by weight (2.0 parts by weight of active ingredient relative to the total solids content) of a non-reactive silicone-based anti-stick agent (BYK-330 (51% active ingredient): manufactured by BYK), and the ink used for the second gloss adjustment layer 6 contained 4.1 parts by weight (2.0 parts by weight of active ingredient relative to the total solids content) of a non-reactive silicone-based anti-stick agent (BYK-330 (51% active ingredient): manufactured by BYK). Apart from the above, the other components were the same as in Example 1, and the decorative material of Comparative Example 2 was produced.
[0113] (Comparative Example 3)
[0114] In Comparative Example 3, the ink used for the first gloss adjustment layer 5 contained 13.2 parts by weight (5.0 parts by weight of active ingredient relative to the total solids content) of a non-reactive silicone-based anti-stick agent (BYK-330 (51% active ingredient): manufactured by BYK), and the ink used for the second gloss adjustment layer 6 contained 9.3 parts by weight (4.5 parts by weight of active ingredient relative to the total solids content) of a non-reactive silicone-based anti-stick agent (BYK-330 (51% active ingredient): manufactured by BYK). Apart from the above, the other components were the same as in Example 1, and the decorative material of Comparative Example 3 was produced.
[0115] (Comparative Example 4)
[0116] In Comparative Example 4, the ink used for the first gloss adjustment layer 5 was provided with 10 parts by weight of a surface-treated silica-based gloss modifier (Mizusawa Chemical Co., Ltd., P-802Y). Apart from the above, the other components were the same as in Example 2, and the decorative material of Comparative Example 4 was produced.
[0117] (Comparative Example 5)
[0118] In Comparative Example 5, the ink used for the first gloss adjustment layer 5 was provided with 10 parts by weight of a surface-treated silica-based gloss adjuster (Mizusawa Chemical Co., Ltd., P-802Y). Apart from the above, the other components were the same as in Example 5, and the decorative material of Comparative Example 5 was produced.
[0119] (evaluate)
[0120] For Examples 1 to 6 and Comparative Examples 1 to 5 above, the anti-sticking and scratch resistance were evaluated.
[0121] <Anti-stickiness (repeated)>
[0122] Attach Sellotape (registered trademark: "Nichiban" brand, 24 mm) to the test piece, press it firmly and evenly onto the test piece, and then quickly peel off the Sellotape at a 90° angle. Repeat the above operation 5 times at the same position. After completion, if there is no peeling such as inter-paper peeling or inter-layer peeling, mark it as "○"; mark it as "△" if there is partial peeling; mark it as "X" if there is peeling. Note that if the evaluation result is "○" or "△", it is considered qualified as there is no problem in use.
[0123] <Anti-sticking property (long-term)>
[0124] Attach Sellotape (registered trademark: "Nichiban" brand, 24 mm) to the test piece, press it firmly and evenly, store it in an environment of 60 °C for 4 days, take it out, cool it to room temperature, and then quickly peel it off at a 90° angle. If there is no peeling such as inter-paper peeling or inter-layer peeling, mark it as "○"; mark it as "△" if there is partial peeling; mark it as "X" if the entire surface is peeled. Note that if the evaluation result is "○" or "△", it is considered qualified as there is no problem in use.
[0125] <Abrasion resistance>
[0126] Use steel wool (#0000) to conduct a 10-cycle abrasion resistance test on the obtained decorative material under a load of 500 g / cm 2 and visually observe whether there are scratches or changes in gloss.
[0127] Then, mark the case where no change in gloss is observed as "◎", the case where a slight change in gloss can be observed as "○", the case where no scratches can be observed but a significant change in gloss can be observed as "△", and the case where scratches or a large change in gloss can be observed as "X". Note that if the evaluation result is "◎", "○" or "△", it is considered qualified as there is no problem in use.
[0128] These evaluation results are shown in Table 1.
[0129] [Table 1]
[0130]
[0131] As shown in Table 1, decorative materials 1 in Examples 1 to 6 can simultaneously achieve both anti-sticking and scratch resistance. On the other hand, for Comparative Examples 1 to 3, when a non-reactive anti-sticking agent was used as the anti-sticking agent contained in the first gloss adjustment layer 5, only long-term anti-sticking performance was evaluated as poor. This is believed to be because the anti-sticking agent has no reactivity with the resin and therefore cannot be fixed within the gloss adjustment layer. During storage at 60°C, the anti-sticking agent seeps out, resulting in poor anti-sticking performance. For Comparative Examples 4 and 5, it is believed that because a surface-treated gloss adjustment agent (i.e., a gloss adjustment agent composed of hydrophobic inorganic materials) was used, the affinity between the gloss adjustment agent and the anti-sticking agent increased, resulting in a relative reduction in the amount of anti-sticking agent present on the surface, thereby reducing anti-sticking performance.
[0132] As can be seen from the above results, the decorative materials of Examples 1 to 6 are decorative materials 1 that simultaneously achieve non-stickiness and scratch resistance.
[0133] It should be noted that the decorative material 1 of the present invention is not limited to the above-described embodiments and examples, and various modifications can be made without departing from the characteristics of the present invention.
[0134] The following is a brief description of decorative materials other than those used in this embodiment, as a reference example.
[0135] Traditionally, decorative materials used for interior and exterior building finishes, doors, windows, furniture, and other surface decorations have been typically finished with wood grain or stone grain patterns. Furthermore, decorative materials that not only display wood grain or stone grain patterns in a flat plane but also three-dimensionally represent the textured surface of natural wood or stone are widely used in applications requiring a high-end feel.
[0136] Various methods have been previously studied for creating planar patterns along with a three-dimensional texture on the surface of decorative materials, used separately depending on the purpose. One method involves not actually creating relief on the surface of the decorative material, but rather using the optical illusion of the human eye to visually represent a three-dimensional effect by altering the surface gloss (specifically, gloss level) of the areas where relief or relief is desired. According to this method, even if no actual relief exists, the human eye can perceive areas with relatively high gloss as relief and areas with relatively low gloss as relief.
[0137] Specifically, for example, a low-gloss transparent or translucent synthetic coating layer is formed on the entire surface of a substrate printed with a suitable pattern including a recessed pattern. Then, a high-gloss transparent or translucent synthetic coating layer is formed on the surface of the formed synthetic coating layer, except for the portion corresponding to the recessed pattern. Of course, if the gloss level is reversed, a decorative material with the recessed and raised surfaces reversed can be obtained.
[0138] According to this method, no special reagents are required; simply by preparing two coatings with different gloss levels, a three-dimensional texture can be easily imparted to any substrate. Furthermore, the formation of the synthetic coating layers with different gloss levels can be achieved using common printing methods such as gravure printing after the pattern (pattern ink layer) has been formed. Therefore, no special equipment is needed, resulting in high production efficiency and easy synchronization with the pattern. Additionally, the synthetic coating layer is much thinner than the desired height difference, thus reducing resin usage and providing better flexibility, enabling the creation of decorative materials with excellent bending adaptability. Moreover, the surface of the decorative material has no large unevenness, preventing contaminants from remaining in the recesses.
[0139] Given the numerous advantages mentioned above, decorative materials employing this method have been widely used. However, in reality, this method still doesn't surpass methods that actually create a textured surface in terms of sophistication. The reason for this might be that, for example, mechanical embossing can faithfully reproduce the textured shape of natural wood, including the cross-sectional shape of its vessels. In contrast, with two different gloss levels of coating, there are two levels of surface gloss, and therefore two levels of texture that can be represented. Thus, it's difficult to reproduce the textured surface of beveled sections with continuously varying depths (heights), such as the vessels of natural wood.
[0140] Therefore, in recent years a decorative material has been proposed that can exhibit textured shapes such as the vessels of natural wood by setting a gloss-adjusting layer (see, for example, Patent Document 1).
[0141] Here, a common method for adjusting the gloss of a gloss-adjusting layer is to add a gloss modifier (matting agent) to a transparent resin used as a binder. Gloss modifiers are primarily made of inorganic or organic microparticles; in particular, inorganic microparticles, such as silica microparticles, are widely used due to their strong matting ability. By adding the gloss modifier, the surface of the gloss-adjusting layer is given an uneven texture, which scatters light, thereby achieving a matting effect. By adjusting the type and amount of these gloss modifiers, the desired gloss can be freely produced.
[0142] From the perspectives of operability, price, and the cohesive strength of the resin itself, urethane resins, often used as adhesives, are frequently employed as transparent resins, employing various polyols and isocyanates. The characteristic of urethane resins is that a variety of properties can be controlled through the combination of polyols and isocyanates. However, due to the relatively large molecular weights of both polyols and isocyanates, and the relatively small number of functional groups per molecule, it is generally difficult to increase the crosslinking density. Crosslinking density is a parameter that significantly affects scratch resistance; therefore, in principle, urethane resins are difficult to meet the requirements for high scratch resistance, such as the scratch resistance required for horizontal surfaces like furniture tops or partitions.
[0143] Furthermore, when using a gloss-modifying layer with the aforementioned gloss modifier, the surface protrusions are selectively scratched during abrasion resistance tests, causing the gloss modifier to detach and resulting in even worse abrasion resistance. Since this tendency to deteriorate abrasion resistance is roughly proportional to the amount of gloss modifier added, it can be said that it is very difficult to meet the abrasion resistance requirements for the aforementioned level surfaces for decorative materials with low gloss and high design complexity.
[0144] On the other hand, it can be considered that ionizing radiation-cured resins with acryloyl or methacryloyl groups, which are transparent resins, have relatively low molecular weights and a high number of functional groups per molecule, resulting in high crosslinking density and easily improved scratch resistance. By using such ionizing radiation-cured resins as transparent resins, decorative materials with excellent scratch resistance can be provided. It should be noted that since scratch resistance mainly depends on the strength of the outermost surface of the decorative material, it is sufficient to use the ionizing radiation-cured resin only as a constituent material of the outermost surface layer.
[0145] However, when the gloss adjusting layer is divided into two layers, and the outermost gloss adjusting layer only covers a portion of the decorative material's surface, the gloss adjusting layer directly below, which covers the entire surface, is also partially exposed. Therefore, to ensure high scratch resistance of the decorative material, it is preferable that both gloss adjusting layers use ionizing radiation-cured resins. Furthermore, in this case, the upper gloss adjusting layer is layered to cover a portion of the lower gloss adjusting layer, which covers the entire surface of the decorative material. However, without ionizing radiation, the ionizing radiation-cured resin will not cure. Therefore, during processing on various printing presses commonly used in the manufacture of decorative materials, a partially covered upper gloss adjusting layer is layered on top of the lower gloss adjusting layer, which covers the entire surface of the uncured decorative material. This can lead to undesirable conditions such as the gloss adjusting layer covering the entire surface dissolving or being scratched.
[0146] On the other hand, the properties required for decorative materials include scratch resistance as mentioned above, and comprehensive durability in daily use. Additionally, in the case of assembled furniture, seals indicating the assembly order are sometimes affixed during packaging; these seals may be removed during or after assembly. Therefore, providing non-stick properties to prevent peeling from the decorative material is also important.
[0147] Adding an anti-stick agent to the gloss-adjusting layer forming the surface of the decorative material is an effective way to impart this non-stick property. However, conventional anti-stick agents use molecularly controlled silicone materials, which, because they do not adhere to the gloss-adjusting layer, tend to detach from the surface of the decorative material over time, resulting in a deterioration in anti-stick properties over time.
[0148] Explanation of symbols
[0149] 1. Decorative materials
[0150] 2 Substrate
[0151] 3. Underlying solid ink layer
[0152] 4-layer patterned ink
[0153] 5. First gloss adjustment layer
[0154] 6. Second gloss adjustment layer
Claims
1. A decorative material, characterized in that it comprises a first gloss adjusting layer disposed on a surface side, and a second gloss adjusting layer disposed on a portion of the first gloss adjusting layer. The first gloss-modifying layer comprises a gloss modifier made of hydrophilic inorganic material and an organosilicon-based anti-sticking agent with reactive ends. The second gloss-adjusting layer comprises a silicone-based anti-stick agent with reactive ends, wherein the reactive ends have at least one acryloyl group. The gloss modifier is composed of particles formed by the secondary aggregation of primary particles.
2. The decorative material according to claim 1, characterized in that the hydrophilic inorganic material as the gloss modifier satisfies (value of evaluation method B / value of evaluation method A) < 1.
2. in, In evaluation method A, the gloss modifier is placed at 110°C for 2 hours, and then the mass loss is measured; in evaluation method B, the gloss modifier is placed at 950°C for 2 hours, and then the mass loss is measured.
3. The decorative material according to claim 1, characterized in that the reactive terminal of the silicone-based anti-stick agent containing the first gloss adjustment layer has at least one of hydroxyl and amino groups.
4. The decorative material according to claim 1, characterized in that the reactive ends of the silicone-based anti-stick agent with reactive ends contained in the first gloss adjustment layer have at least hydroxyl groups.
5. The decorative material according to any one of claims 1 to 4, characterized in that, relative to 100 parts by mass of the solid components constituting the first gloss adjustment layer, the amount of the silicone-based anti-stick agent added to the first gloss adjustment layer is such that the effective component of the silicone-based anti-stick agent is in the range of 1 part by mass to 6 parts by mass.
6. The decorative material according to any one of claims 1 to 5, characterized in that the main material of the resin component constituting the first gloss adjustment layer is a mixture of a urethane thermosetting resin having polyols and isocyanates and an ionizing radiation curing resin having acryloyl groups or methacryloyl groups, wherein the urethane thermosetting resin comprises, relative to 100 parts by mass of the ionizing radiation curing resin, 3 to 100 parts by mass of the urethane thermosetting resin.
7. The decorative material according to any one of claims 1 to 6, characterized in that the reactive ends of the silicone-based anti-stick agent containing reactive ends in the second gloss adjustment layer further have methacryloyl groups.
8. The decorative material according to any one of claims 1 to 7, characterized in that, relative to 100 parts by mass of the solid components constituting the second gloss adjustment layer, the amount of the silicone-based anti-stick agent added to the second gloss adjustment layer is such that the effective component of the silicone-based anti-stick agent is in the range of 0.5 parts by mass to 5 parts by mass.
9. The decorative material according to any one of claims 1 to 8, characterized in that the main material of the resin component constituting the second gloss adjustment layer is a mixture of a urethane thermosetting resin having polyols and isocyanates and an ionizing radiation curing resin having acryloyl groups or methacryloyl groups, comprising 25 parts by mass or less of the urethane thermosetting resin relative to 100 parts by mass of the ionizing radiation curing resin.
10. The decorative material according to any one of claims 1 to 8, characterized in that the main material of the resin component constituting the second gloss adjustment layer is an ionizing radiation-cured resin having acryloyl or methacryloyl groups.
11. The decorative material according to claim 6, claim 9 or claim 10, characterized in that the number average molecular weight of the ionizing radiation-cured resin having acryloyl or methacryloyl groups is in the range of 300 to 5000.
12. The decorative material according to claim 11, characterized in that the number average molecular weight of the ionizing radiation-cured resin having acryloyl or methacryloyl groups is 300 or more and 1500 or less.
13. The decorative material according to any one of claims 1 to 12, characterized in that a patterned ink layer is provided on the underside of the first gloss adjusting layer. When viewed from the surface side, the second gloss adjustment layer is formed in the portion that overlaps with the pattern of the patterned ink layer, and the gloss of the patterned ink layer is synchronized with that of the second gloss adjustment layer.
14. The decorative material according to any one of claims 1 to 12, characterized in that a patterned ink layer is provided on the underside of the first gloss adjusting layer. The second gloss adjustment layer is formed in the portion of the patterned ink layer excluding the area directly above the pattern, and the gloss of the patterned ink layer is synchronized with that of the first gloss adjustment layer.
15. The decorative material according to claim 1, characterized in that, The amount of the silicone-based anti-stick agent added to the first gloss adjusting layer, relative to 100 parts by weight of the solid components constituting the first gloss adjusting layer, is such that the effective component of the silicone-based anti-stick agent is in the range of 5.0 parts by weight to 6.5 parts by weight. The amount of the silicone-based anti-stick agent added to the second gloss adjustment layer, relative to 100 parts by weight of the solid components constituting the second gloss adjustment layer, is such that the effective component of the silicone-based anti-stick agent is in the range of 4.5 parts by weight to 5.5 parts by weight. The amount of silicone-based anti-sticking agent added to the first gloss adjustment layer is greater than the amount of silicone-based anti-sticking agent added to the second gloss adjustment layer.